2015
DOI: 10.5194/se-6-403-2015
|View full text |Cite
|
Sign up to set email alerts
|

Soil aggregation, erodibility, and erosion rates in mountain soils (NW Alps, Italy)

Abstract: Abstract. Erosion is a relevant soil degradation factor in mountain agrosilvopastoral ecosystems that can be enhanced by the abandonment of agricultural land and pastures left to natural evolution. The on-site and off-site consequences of soil erosion at the catchment and landscape scale are particularly relevant and may affect settlements at the interface with mountain ecosystems. RUSLE (Revised Universal Soil Loss Equation) estimates of soil erosion consider, among others, the soil erodibility factor (K), wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 41 publications
0
46
0
Order By: Relevance
“…As noted earlier, this would suggest that better soils also have higher resistance against land degradation, albeit that other unobserved effects might be at play as well. The reason that productive soils are more resistant against degradation processes like water (Stanchi et al, 2015) and wind erosion (Herrick and Beh, 2015) is closely related to prevailing aggregate stability (Colazo and Buschiazzo, 2010) that determines important soil production properties like infiltration and permeability while protecting soils against dispersive water and wind forces (Jozefaciuk and Czachor, 2014;Geng et al, 2015). Organic matter that acts as a binding agent and nucleus in the formation of aggregates is the most important component of soil aggregate stability.…”
Section: Resultsmentioning
confidence: 99%
“…As noted earlier, this would suggest that better soils also have higher resistance against land degradation, albeit that other unobserved effects might be at play as well. The reason that productive soils are more resistant against degradation processes like water (Stanchi et al, 2015) and wind erosion (Herrick and Beh, 2015) is closely related to prevailing aggregate stability (Colazo and Buschiazzo, 2010) that determines important soil production properties like infiltration and permeability while protecting soils against dispersive water and wind forces (Jozefaciuk and Czachor, 2014;Geng et al, 2015). Organic matter that acts as a binding agent and nucleus in the formation of aggregates is the most important component of soil aggregate stability.…”
Section: Resultsmentioning
confidence: 99%
“…Acceleration of soil erosion rates is the result of increased runoff on soil surfaces that are vulnerable to soil detachment (Van Oost et al, 2009). If a soil has characteristics (Stanchi et al, 2015) that prohibit infiltration of water (e.g. crusting, slacking, lack of macro pores) the runoff coefficient will be higher (Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In line with these results, Trabaquini et al (2015) showed that land degradation in Brazilian savannah (Cerrado) has altered the soil's physical attributes, increasing runoff; bulk density and penetration resistance, whereas air permeability and porosity decreased. Tang et al (2016) observed that areas with larger aboveground biomass have higher aggregate stability which has correlation with erosion-related variables, especially soil erodibility (Stanchi et al, 2016). The observed reduction of ΔOC and increased land cover may be an indication of an increase in the carbon stock in H F , which improved soil's physical conditions such as aggregate stability, infiltration, porosity and water storage capacity (Stanchi et al, 2016;Costantini et al, 2016).…”
Section: Discussionmentioning
confidence: 99%